Eucaristia e anúncio - Miranda, Mario de França (Revista Eclesiástica Brasileira, 2008)
O Autor confronta a celebração eucarística com a pregação da Palavra e mostra como ambas as realidades partem da mesma raiz. Este confronto nos ajudará a melhor entender o sentido de cada uma delas, como também o da homilia no interior da Eucaristia. Enfim, aponta para algumas conseqüências pastorais decorrentes desta reflexão. Abstract: The Author compares the Eucharistic celebration with the preaching of the Word and shows that both realities spring from the same root. This comparison will contribute to a greater understanding of the meaning of each of these realities and also of the homily within the Eucharistic itself. Finally he points to some pastoral consequences of this reflection.